Perbaikan Kesalahan Pemahaman Konsep Pecahan di Sekolah Dasar - H.M. Zainuddin (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1999)
The concept of fraction in the 1994 curriculum begins to be introduced to the second and the third year students of elementary school. However, students often get difficulty understanding it. An informal interview with teachers of SDN Sentul VI Blitar indicates that students often misunderstand the concept of fraction. This action research was intended to correct students’ misunderstandings in comparing two fractions by way of interview, observation, and tests. The results show that introducing the concept of fraction by dividing things into two may result in different perception between teachers and students.